2004
DOI: 10.1111/j.1439-0469.2004.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

A new look at geographic and phylogenetic relationships within the species group surrounding Octopus vulgaris (Mollusca, Cephalopoda): indications of very wide distribution from mitochondrial DNA sequences

Abstract: The distribution of Octopus vulgaris has not yet been completely clarified. For a long time, a cosmopolitan distribution with unknown distribution limits had been assumed. This assumption has recently been questioned and it has been postulated that the distribution is restricted to the Mediterranean and the northeastern Atlantic. However, as our previous studies show, the existence of O. vulgaris can be confirmed for the Mediterranean and the whole eastern Atlantic, and evidence is provided for its occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
2
31
0
7
Order By: Relevance
“…Some authors estimate that the occurrence of this species is restricted to Mediterranean and the East portion of the Atlantic Ocean (Belcari et al 2002). However, DNA studies of distant populations have confirmed the occurrence of the same species also in western Atlantic Ocean and northwest of Pacific (Warnke et al 2004). …”
Section: The Biological Classification Of Octopi Is Quite Com-mentioning
confidence: 99%
“…Some authors estimate that the occurrence of this species is restricted to Mediterranean and the East portion of the Atlantic Ocean (Belcari et al 2002). However, DNA studies of distant populations have confirmed the occurrence of the same species also in western Atlantic Ocean and northwest of Pacific (Warnke et al 2004). …”
Section: The Biological Classification Of Octopi Is Quite Com-mentioning
confidence: 99%
“…O. tehuelchus appears more closely related to the genera Callistoctopus, Grimpella and Macroctopus, as well as to "unplaced" Octopus species sensu Norman and Hochberg (2005), than to the clade containing most of the valid species of Octopus (Fig. 1) Söller et al (2000) and Warnke et al (2004) and identified as a new species, O. insularis, by Leite et al (2008) In the last few years, studies on the molecular systematics of octopuses have helped to clarify their confusing systematics and phylogenetic relationships and also to identify and describe new species (Norman and Hochberg 2005, Allcock et al 2007, Leite et al 2008, Strugnell et al 2009). In the present study, we focused on the genus Octopus using a Bayesian approach to estimate the phylogenetic relationships among published sequences of the COIII gene of Octopus species, of O. tehuelchus from the southwestern Atlantic Ocean (a species never included in phylogenetic analyses of the genus before), and of individuals of O. mimus from newly sampled localities in the Pacific Ocean (Chile and Peru).…”
Section: Resultsmentioning
confidence: 99%
“…vulgaris specimens are included in two different, well-supported clades, with O. insularis as their sister group. These specimens were considered by Söller et al (2000) and Warnke et al (2004) as part of the O. vulgaris species complex, but Leite et al (2008) described them morphologically, established their molecular distinctiveness and phylogenetic position using the 16S rRNA gene, and assigned them the name O. insularis. In the papers by Söller et al (2000) these specimens group with other O. vulgaris forming a monophyletic clade, but they do not include other species of Octopus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations